KAJIAN LITERATUR TRANSFORMASI PEDAGOGIS SATUA I LUTUNG TEKEN I KAKUA TERHADAP PENGUATAN KARAKTER DAN LITERASI DI SEKOLAH DASAR - Ida Bagus Yoga Swadnyana; I Wayan Sujana; Ida Bagus Teja Mahotama; I Ketut Aris Adi Saputra; Putu Edi Adnyan; I Putu Purwadi Putra (STKIP Subang, 2026)
Moral degradation and low cultural literacy are serious challenges in today's modern education ecosystem. This article aims to synthesize various research findings related to the use of Balinese folklore, specifically Satua I Lutung Teken I Kakua, as a medium for character and literacy learning. The design used was a literature review of national journal articles from the 2021-2026 period. Based on the study results, it was found that social situations and integrity degradation can be mitigated through the integration of local wisdom into digital media such as flipbooks and e-modules. The results indicate that this satua is effective in instilling the value of honesty and improving reading comprehension through innovative methods. The role of educators in this model is to facilitate critical discussions to explore students' value systems and literacy potential.